How to increase the efficiency of receiver-driven adaptive mechanisms in a new generation of IP networks - Mendes, Paulo (2004)
Receiver-driven adaptation allows streaming of multicast multimedia content to different receivers across networks with heterogeneous characteristics, such as different resource availability. However, receivers are only encouraged to adapt if network providers guarantee a fair distribution of bandwidth and also the punishment of receivers that do not adjust their rate in case of congestion. Therefore, we define a receiver-driven adaptive mechanism based on a new fairness protocol that provides the required guarantees for adaptation in heterogeneous networks. We use simulations to evaluate the proposed mechanism and to compare its performance with other receiver-driven mechanisms. Our work contributes to show that the problems of receiver-driven adaptation, such as the induction of losses, can be solved even with simple receiver-driven adaptive mechanisms, when a fair allocation of resources in provided by the network.